Destiny (Al-Qadr) in the Qur'an: An Epistemological and Theological Exploration of Divine Decree and Human Responsibility - Andi Syahrul; Muh. Yusuf; Hasyim Haddade (Pustaka Digital Indonesia, 2025)
In Islamic theology, the concept of destiny (qadar) is a fundamental tenet of faith, representing one of the six pillars that guide every Muslim's belief system. Destiny is understood as the divine decree of Allah SWT, encompassing all events—large and small—predetermined since the beginning of creation. However, this understanding does not equate to passive acceptance; rather, it serves as a foundation that encourages Muslims to strive earnestly and pursue their aspirations. The Qur'an frequently references destiny, often in the context of natural laws and causality, highlighting that divine decrees underpin the order and predictability of the universe. While Allah's will is absolute, humans are granted the freedom to choose their actions, thereby bearing moral responsibility for their choices and their consequences. This balance between divine determination and human agency forms the basis for justice, equality, and the dignity of humankind in Islam. The term